The Strange Case of Billy Biswas: Two conflicting realities - Mantri Venkata Raghu Ram; Bikki Anupama (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2017)
Arun Joshi presents socio-cultural conflicts between two different societies. One society is material driven and backed by the modern state apparatus like police, courts, etc. while the other is subsistence driven and is at the bottom in the hierarchy of the modern state. Indian tribal societies have been exploited right from the colonial period into the post-independence times. These two societies differ as follows: the tribal society lives on subsistence looks at Nature as a space for socio-economic, political, cultural and community, while the urban materialistic world perceives Nature as a resource to be exploited. This primordial difference has manifested as a socio-cultural conflict between these two societies. This may be due to the mutually exclusive and incorrigible nature of their social constructs which trigger perceptual obfuscation of symbiotic living. What appears to be an objective reality for one appears as subjective to the other and vice versa. This paper studies the strangeness of Billy Biswas, the protagonist of the novel in the socio-cultural milieu of conflicting realities.